6(z-5)=24

Simple and best practice solution for 6(z-5)=24 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(z-5)=24 equation:


Simplifying
6(z + -5) = 24

Reorder the terms:
6(-5 + z) = 24
(-5 * 6 + z * 6) = 24
(-30 + 6z) = 24

Solving
-30 + 6z = 24

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '30' to each side of the equation.
-30 + 30 + 6z = 24 + 30

Combine like terms: -30 + 30 = 0
0 + 6z = 24 + 30
6z = 24 + 30

Combine like terms: 24 + 30 = 54
6z = 54

Divide each side by '6'.
z = 9

Simplifying
z = 9

See similar equations:

| -2+8u=-50 | | 296+x-24+29=360 | | -2(5s+2)+5(s-3)= | | 5x+3=8x+2 | | N/5-(-11)=9 | | 13.5(n)=189 | | 8-x/5=22 | | -11-12g=-71 | | 9(4-s)=10+45 | | 2(2)+3x=24 | | 40(n)=324 | | 34-8x=16+10x | | Y^2-2y+5-8y+10=0 | | 5(h-2)-6(h+1)= | | x+17+2x+1=90 | | 3(n)=210 | | -165=13a | | 17(b-4)= | | 200=x^3+4x^2+4x | | X-2=11/24 | | 22x-3=20+10x | | F/10-11=9 | | 18=9x-7 | | L=1+-3w | | 4(4x-4)=-144 | | 5(n)=126 | | 7+4(x-4)-10=-45 | | 3+3x=4x+20 | | 13=×/3-22 | | 50/X-60=51.666 | | 2x-15+3(x-1)=13 | | 2x+3(8)=24 |

Equations solver categories